The Influence of Physical Culture on The Comprehensive Development and Adaptation of Children with Special Educational Needs in The Context of Social Relationships - Staneva, Svetlana (Journal of Danubian Studies and Research, 2023)
In the article there is a description of the physical and recreational work at the secondary education institution No. 8 in Izmail. We found out that under physical culture and health technology we consider not only the process of using physical education tools for the purpose of improving students, but also the basis of the methodology of building a physical culture and health process. We came to the conclusion that the use of health-saving educational technologies in the process of adaptive physical culture of students with special educational needs at the primary level of education requires the prevention of the occurrence of health risk factors for schoolchildren; individual approach in the process of physical education.